The Philosophical And Scientific Essence Of The Relationship Between Teacher And Student In The Works Of The Sufi Olloyor (Diversity Research: Journal of Analysis and Trends, 2026)
This article analyzes the philosophical and scholarly essence of the mentor– disciple relationship as reflected in the works of Sufi Olloyor. Particular attention is given to the conceptual foundations of spiritual education, moral perfection, and intellectual discipline in the classical Sufi tradition. The study interprets the mentor–disciple model not only as a religious and ethical phenomenon, but also as a pedagogical and epistemological system that shapes personal development and social responsibility. Sufi Olloyor’s views are examined in the context of Islamic moral philosophy, emphasizing the role of the teacher as a guide toward truth, self-purification, and knowledge. The article also highlights the disciple’s duties, such as sincerity, respect, patience, and commitment to self-improvement, which are presented as necessary conditions for attaining both spiritual and intellectual maturity. As a result, the research demonstrates that the mentor–disciple relationship in Sufi Olloyor’s heritage represents a holistic educational paradigm integrating faith, morality, and rational understanding.